Evaluation of tomato (Solanum lycopersicum) genotypes for plant growth, fruit yield and quality - KHAN, F A; BHAT, HILAL A; BHAT, S A; NARAYAN, S; MIR, S A; Z MASOODI, KHALID; MALIK, A A; LONE, S A; SAJAD, SEHRISH; JAN, URFIA (The Indian Journal of Agricultural Sciences, 2022)
The study was carried out with different tomato (Solanum lycopersicum L.) genotypes during 2018 and 2019 at Division of Basic Sciences and Humanities (SKUAST-K), Shalimar, Srinagar (J&K) to assess the plant and fruit growth with quality characters and mineral composition. Healthy and uniform seedlings of twelve tomato genotypes were transplanted in pots with four replications. Among different genotypes, 2016/TODVAR-9 (G8) recorded the highest leaf area (713.6 cm2) and fruit yield (1.77 kg/plant) that also showed maximum values TSS (4.35%), titrable acidity (1.32%), vitamin C (36.18 mg/100g), lycopene (6.84 mg/100g) and carotenoid (8.28 mg/100g) contents coupled with maximum P (0.83%), K (2.35%), Mg (0.52%) and Ca (0.23%) contents. Regression analysis of the data showed a strong correlation between leaf area and fruit yield (r = 0.86**), leaf area and fruit sugar content (r = 0.60*), PLW and fruit Ca content (r = -0.97**), fruit Ca content and storage life (r = 0.97**) and fruit PLW and storage life (r = -0.98**)